Understanding Predictors of Over-Optimism in IS Project Teams. Issue 1 (2nd January 2020) - Korzaan, Melinda; Harris, Amy
ABSTRACT: The primary objective of this study is to examine the influence that psychological factors have on project team members' degree of over-optimism regarding successful project completion. Specifically, we examine the impact that select personality traits and psychological states have on project team members' degree of over-optimism about bringing a project to a successful completion. A field survey methodology was employed to survey IT project team members from Fortune 500 companies and the research model was tested using structural equation modeling. Results indicate that project-specific self-efficacy has both a direct positive effect on over-optimism and an indirect effect via the implementation mindset construct. General self-efficacy was demonstrated to directly influence project-specific self-efficacy and indirectly influence over-optimism via the implementation mindset construct. Preference for consistency was also demonstrated to have a direct effect on over-optimism. Implications for developing interventions to minimize the impacts of over-optimism related to IT projects are discussed.